Banana diploids (AA) submitted to salt stress - Gomes, Eline Waked Ferreira; Willadino, Lilia; Martins, Luiza Suely Semen; Silva, Sebastião de Oliveira e; Camara, Terezinha Rangel; Meunier, Isabelle Maria Jaqueline (Pesquisa Agropecuaria Brasileira, 2004)
In the Northeast Region of Brazil, salinization in soils is one of the limiting factors for banana production. Studies regarding tolerance and salt sensitivity in banana diploids are important for genetic breeding programs. This work aimed to evaluate salt stress effects measuring growth and chemicals parameters and to quantify the genetic diversity among six diploids (AA) genotypes using isozymic standards relating to salt tolerance. The plants were treated during 21 days under 0, 50 and 100 mM of NaCl in a completely randomized design. The diploids Lidi and Calcuttá presented the greatest leaf area reduction and severe toxicity associated to greater Na+ and Cl- accumulation in leaf blades. The genotypes Borneo and SNº/2 presented discrete symptoms of toxicity and like M-53 genotype, demonstrated the capacity of avoiding excessive translocation of Na+ and Cl- to the leaves preserving the photosynthetic apparatus. Only the diploid SNº/2 and M-53 showed a specific peroxidase band (Po-6), under salt stress. The relationship between the isoenzymatic and the growth and mineral analysis of vegetal tissue created dendrograms separating the most tolerant genotypes (SNº/2 and M-53) from the most sensitive ones (Lidi and Calcuttá).